STFE-Net:Enhanced Deep Learning for Real-Time Abnormal Behavior Detection in Video Surveillance - Chen, Cong; Fu, Xianjun; Li, Yi (Informatica, 2025)
A spatiotemporal feature enhancement network (STFE-Net) is proposed for real-time abnormal behavior detection in surveillance video. The model integrates optimized 3D convolution kernels, a multi-scale convolution strategy, and a feature fusion module with skip connections and attention mechanisms, followed by an improved fully connected classification structure. STFE-Net achieves an average accuracy of 0.85 on the UCF-Crime dataset and 0.82 on multiple datasets, outperforming traditional 3D-CNNs (average 0.65) and RNN-based models (average 0.68). False alarm rates are reduced to 0.10 and false negative rates to 0.07, demonstrating improved precision and robustness. Compared with baseline methods, STFE-Net shows a 26.2% increase in average accuracy and up to 50% reduction in false positives, significantly improving real-time surveillance reliability.